Facial Emotion Recognition in Psychosis and Associations With Polygenic Risk for Schizophrenia: Findings From the Multi-Center EU-GEI Case–Control Study. (23rd March 2022) - Tripoli, Giada; Quattrone, Diego; Ferraro, Laura; Gayer-Anderson, Charlotte; La Cascia, Caterina; La Barbera, Daniele; Sartorio, Crocettarachele; Seminerio, Fabio; Rodriguez, Victoria; Tarricone, Ilaria; Berardi, Domenico; Jamain, Stéphane; et al.
Abstract: Background and Hypothesis: Facial Emotion Recognition is a key domain of social cognition associated with psychotic disorders as a candidate intermediate phenotype. In this study, we set out to investigate global and specific facial emotion recognition deficits in first-episode psychosis, and whether polygenic liability to psychotic disorders is associated with facial emotion recognition. Study Design: 828 First Episode Psychosis (FEP) patients and 1308 population-based controls completed assessments of the Degraded Facial Affect Recognition Task (DFAR) and a subsample of 524 FEP and 899 controls provided blood or saliva samples from which we extracted DNA, performed genotyping and computed polygenic risk scores for schizophrenia (SZ), bipolar disorder (BD), and major depressive disorder (MD). Study Results: A worse ability to globally recognize facial emotion expressions was found in patients compared with controls [ B = −1.5 (0.6), 95% CI −2.7 to −0.3], with evidence for stronger effects on negative emotions (fear [ B = −3.3 (1.1), 95% CI −5.3 to −1.2] and anger [ B = −2.3 (1.1), 95% CI −4.6 to −0.1]) than on happiness [ B = 0.3 (0.7), 95% CI −1 to 1.7]. Pooling all participants, and controlling for confounds including case/control status, facial anger recognition was associated significantly with Schizophrenia Polygenic Risk Score (SZ PRS) [ B = −3.5 (1.7), 95% CI −6.9 to −0.2]. Conclusions: Psychosis is associated with impaired recognition of fear and anger, and higher SZ PRS is associated with worse facial anger recognition. Our findings provide evidence that facial emotion recognition of anger might play a role as an intermediate phenotype for psychosis.